A Capability View of Success in Quintile 1 Schools in South Africa. (1st April 2016) - Maarman, Rouaan
Abstract: The success of Quintile 1 schools in South Africa has attracted many diverse interpretations especially as the single variable of Grade 12 results are commonly used as the yardstick to compare performance between schools. Although this approach serves a purpose, it can also bemisleading as these results provide a simplified snapshot of success, leaving the actual process of achieving success as a wide terrain open to contestation. In this paper the researcher attempts to contribute to these views by problematizing success from the perspective of Quintile 1 schools using a capability analysis based on Amartya Sen's normative framework. The paper shows that understanding capabilities and functioning, as described by Sen brings into focus both philosophical and practical reasoning about success in South African schools. The application of the capability approach in educational analysis has been fairly limited, but the paper shows that it does provide robust theoretical constructs to evaluate social justice issues differently.